Polish Popular Music on Screen - Mazierska, Ewa. author. aut Link
XII, 321 p. 23 illus., 18 illus. in color.
Keywords: This book examines the interface between Polish popular music and screen media against the background of Polish history, cinema, and popular culture and situates that interface in a local as well as global context. It looks at Polish musicals, biographical films about musicians, documentary films and, finally, music videos. The author draws attention to the immense popularity of musical comedies in Polish interwar cinema, the enduring appeal of musical genres during the period of state socialism, despite their low status in film criticism, and the re-birth of musicals in the 2010s. Mazierska also discusses the most important stars, directors and authors of songs presented in Polish films, and points to the effect of technological changes on inception and transformation of music-centred genres of screen media, including the effect of YouTube on their growth and preservation. The book is informed by the question of how parochial and universal is Polish popular music and its screen representation.